Evaluation of morphodynamic changes in the vicinity of low-crested breakwater on cohesive shore of carey island, Malaysia - Fitri, A.; Hashim, R.; Song, K.; Motamedi, S. (2015)
There is no adequate research available on the responses of coastal morphodynamic to low-crested breakwaters along the cohesive shore. Since the shore responses to coastal structures vary widely among different case studies, it is necessary to evaluate the performance of these structures before they are chosen as a coastal protection alternative. In the present study, we investigated the bed level changes and the accretion-erosion pattern on intertidal area of the cohesive shore in Malaysia due to the presence of low-crested breakwater from the year 2009 to 2014. The bathymetry data was obtained during a project in Carey Island, Malaysia. The results showed that the existing breakwater have successfully increased the bed level behind the structure. The increase of sediment accumulation have reached 0.176m(3)/m2 five years after the construction of the breakwater. However, the increased bed level five years after its installation is still not sufficient to fulfill the required bed level and hydraulic regime for the mangroves survival. Thus, the bed levels need to be increased further to establish a suitable hydraulic regime for the mangrove rehabilitation project at the site